Associated factors for infant Pertussis death in Sabah, Malaysia - Abraham Chiu En Loong; Mohd Yusof Ibrahim; Abdul Rahman Ramdzan (Universiti Putra Malaysia, 2024)
Introduction: Pertussis remains a significant public health concern globally, particularly for infants, who are at higher risk of severe disease and mortality. Despite the availability of vaccines, pertussis cases and deaths persist, with recent resurgences reported worldwide. This study aims to identify factors associated with infant pertussis mortality in Sabah, Malaysia, to inform targeted interventions and public health strategies. Materials and methods: A cross-sectional study design was employed, utilizing communicable disease notification data from 2016 to 2020 in Sabah. Descriptive and statistical analyses were conducted to investigate the association between sociodemographic characteristics, pertussis vaccination status, and infant pertussis death. Results: A total of 323 infant pertussis cases were included in the study. Factors significantly associated with pertussis mortality included gender and pertussis vaccination status. Female infants had 2.67 times higher odds of mortality (95% CI: 1.132, 6.288 , p = 0.025), while infants fully vaccinated for age had a 79.4% reduced likelihood of death (AOR: 0.206, 95% CI: 0.074, 0.576, p = 0.003). Conclusion: Our study underscores the importance of gender-sensitive healthcare and complete vaccination in reducing infant pertussis mortality. Strategies emphasizing gender base approaches, timely vaccination and early protective measures are essential to mitigate pertussis-related deaths in Sabah.